Health care system in bangladesh - Dibyajyoti Saha (Research Center for Rational Use of Drugs (RCRUD), 2015)
Pharmacists are healthcare professionals who practice in pharmacy, the field of health sciences focusing on safe and effective medication use. The role of pharmacist has shifted from the classical "lick, stick and pour" dispensary role, to being an integrated member of the health care team directly involved in patient care. But, in our country pharmacists are mainly engaged with manufacturing of drugs, which is secondary responsibility of pharmacist.